Pessoas com deficiência mental agravada e regime jurídico das incapacidades : contribuições de uma ética da vulnerabilidade - Carvalho Neto, Wilson Botelho de (2024)
The autonomy granted to people with disabilities proves insufficient to ensure equal opportunities in all aspects of life when confronted with social reality, especially in the case of individuals with aggravated mental disabilities. This is because the concept of autonomy, often corrupted, is perceived in the legal framework as independence, self-sufficiency, and the ability to perform actions. This work aims to demonstrate whether the changes in the incapacity regime, introduced by the Statute of Persons with Disabilities, have bound individuals with aggravated mental disabilities to this notion of autonomy, or if there is a possibility of reformulating this concept of self-sufficiency by applying a new paradigmatic perspective related to the ethics of vulnerability proposed by Corine Pelluchon. The deductive method will be employed, starting with a documentary and bibliographic analysis, and drawing on an examination of official statistical data. In the first chapter, an intersection will be made between the condition of a person with a disability and social vulnerability, exploring the evolution of terminology related to this minority group and the transition from the medical model to the social model of disability. It will also highlight the need to confront ableism and the various vulnerabilities faced by these individuals. In the second chapter, the research will focus on the rights of people with disabilities, examining both the international and national landscapes. It will delve into the alteration of the incapacity regime from the perspective of the Statute of Persons with Disabilities to understand the necessary legal protection for those with severe mental impairment. In the third chapter, the ethics of vulnerability will be explored in contrast to the ethics of autonomy, from Corine Pelluchon's perspective. It will investigate the paradox present in the incapacity regime and the duality between the two ethics. Finally, the applicability of the ethics of vulnerability in cases of individuals with aggravated mental disabilities will be discussed, emphasizing the need to reconfigure the notion of autonomy. This reconfiguration goes beyond the simple ability to perform tasks; it primarily involves the power to express one's own desires and values without losing autonomy. Thus, it aligns with the vulnerability of the person with a disability, recognizing and respecting the uniqueness of their experiences and perspectives.